Diosgenin normalization of disrupted behavioral and central neurochemical activity after single prolonged stress - Malik, Hurmat; Usman, Muhammad; Arif, Mehreen; Ahmed, Zainab; Ali, Gowhar; Rauf, Khalid; Sewell, Robert D. E. (Frontiers in Pharmacology, 2023)
Abstract Post-traumatic stress disorder (PTSD) is a chronic mental illness triggered by traumatic experiences such as wars, natural disasters, or catastrophes, and it is characterized by anxiety, depression and cognitive impairment. Diosgenin is a steroidal sapogenin with known neuroprotective and antioxidant properties. This study aimed to assess the pharmacological potential of diosgenin in a single prolonged stress (SPS) model of PTSD, plus other behavioral models along with any consequent alterations in brain neurochemistry in male mice. SPS was induced by restraining animals for 2 hours, followed by 20 minutes of forced swim, recuperation for 15 minutes, and finally, exposure to ether to induce anesthesia. The SPS-exposed animals were treated with diosgenin (20, 40, and 60mg/kg) and compared with the positive controls, fluoxetine or donepezil, then they were observed for any changes in anxiety/depression-like behaviors, and cognitive impairment. After behavioral screening, postmortem serotonin, noradrenaline, dopamine, vitamin C, adenosine and its metabolites inosine and hypoxanthine were quantified in the frontal cortex, hippocampus, and striatum by high-performance liquid chromatography. Additionally, animal serum was screened for changes in corticosterone levels. The results showed that diosgenin reversed anxiety- and depression-like behaviors, and ameliorated cognitive impairment in a dose-dependent manner. Additionally, diosgenin restored monoamine and vitamin C levels dose-dependently and modulated adenosine and its metabolites in the brain regions. Diosgenin also reinstated otherwise increased serum corticosterone levels in SPS mice. The findings suggest that diosgenin may be a potential candidate for improving symptoms of PTSD.